Effectiveness of Integration of Exit Slips Formative Assessment in Problem Based Learning in Improving Critical Thinking Skills of High School Students on Heat Material - Amara, Wina; Ridwan Efendi; Amsor (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
This study was motivated by the need to address the lack of critical thinking skills among students in order to meet the demands of the 21st century. The purpose of this study was to demonstrate the effectiveness of integrating formative assessment in the form of Exit Slips into problem-based learning to improve students' critical thinking skills related to current issues. The research design used was quasi-experimental with matching only pretest posttest  control group, involving 69 eleventh-grade students in Bandung. Data were collected using the ACTA test for critical thinking, formative assessment called Exit Slips, and student questionnaires. Data analysis was conducted using the N-Gain test, effect size, and quantitative descriptive analysis. The results of the study showed a significant difference in the improvement of critical thinking skills between the experimental group and the control group, with N-Gain values in the moderate category and effect sizes in the high category. Student responses to the integration of Exit Slips formative assessment into problem based learning were also in the good category. Overall, the integration of Exit Slips formative assessment into problem-based learning was highly effective in improving critical thinking skills.